2017
DOI: 10.1038/cddis.2017.440
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in breast cancer: novel diagnostic and prognostic biomarkers

Abstract: Effective management of breast cancer depends on early diagnosis and proper monitoring of patients’ response to therapy. However, these goals are difficult to achieve because of the lack of sensitive and specific biomarkers for early detection and for disease monitoring. Accumulating evidence in the past several years has highlighted the potential use of peripheral blood circulating nucleic acids such as DNA, mRNA and micro (mi)RNA in breast cancer diagnosis, prognosis and for monitoring response to anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
258
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(263 citation statements)
references
References 138 publications
1
258
0
4
Order By: Relevance
“…Numerous studies have been reported that miRNAs have regulatory functions in pathological processes, in particular in the development and progression of tumors . Hence, it is possible that many miRNAs could serve as biomarkers for the diagnosis of different types of cancer, including BC …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been reported that miRNAs have regulatory functions in pathological processes, in particular in the development and progression of tumors . Hence, it is possible that many miRNAs could serve as biomarkers for the diagnosis of different types of cancer, including BC …”
Section: Discussionmentioning
confidence: 99%
“…miRNAs may play a crucial role a class of oncogenes or tumor suppressor genes in cancer . In BC, miRNA profiling has allowed for the identification of biomarker signatures associated with the diagnosis, staging, progression, and prognosis …”
Section: Introductionmentioning
confidence: 99%
“…The predictive and prognostic value of miRNAs has been investigated in breast cancer . In a small study (n = 11), Kolacinska et al found higher expression of miR‐200b‐3p/miR‐190a along with lower expression of miR‐512‐5p in breast cancer tissue before chemotherapy correlated with a better pathologic response to NCT.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] MiRNA is reported to be involved in diverse biological processes, such as cell proliferation, apoptosis and death. 7 Abnormal miRNA expression has been frequently observed in various human cancers, either as an oncogene or a tumor-suppressor.…”
mentioning
confidence: 99%